Pelatihan Pengolahan Wortel Menjadi Stick Sehat Pengontrol Kadar Glukosa Darah Bagi Ibu PKK di Desa Temulus Mejobo Kudus - Rifda Naufa Lina; Annis Rahmawaty; Heni Setyoningsih; Hasty Martha Wijaya; Yulia Pratiwi; Dian Arsanti Palupi; Lilis Sugiarti; Chabbah Tri Septian; Wara Madia (Jurnal Pengabdian Bidang Kesehatan, 2024)
Carrots are a type of tuber vegetable that is rich in antioxidant compounds, including vitamin C and beta carotene. One of the functions of antioxidants is to protect pancreatic beta cells from free radical attacks and is also a vasodilator in preventing cardiovascular disorders Damage to pancreatic beta cells can result in high blood glucose levels. Carrots have a taste are not pleasant to consume, so they are made in stick form, which is a snack that is easy to consume every day with a delicious taste and is effective in controlling blood glucose levels. The aim of this activity is to increase the knowledge, skills of PKK’s mother in Temulus about the benefits of carrots and how to process them into healthy sticks so they are delicious to consume. The methods used are descriptive, explanation, discussion and practice. The result of this activity was an increase in knowledge from the good category of 10% (3 people) to 46.67% (14 people) with a total of 30 participants. The conclusion of this activity is the increasing knowledge of PKK mothers in Temulus about the benefits of carrots as controlling blood glucose levels and increasing the skills of PKK mothers in Temulas in processing carrots into healthy sticks to control blood glucose levels.